2020
DOI: 10.1002/curj.25
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in current curriculum reform and the development of teachers’ professional autonomy

Abstract: Current curriculum reform in Wales provides an opportunity for teachers to have greater freedom to develop pedagogical approaches that meet the needs of their pupils. The Successful Futures report recommends that teachers should have a greater autonomy in choosing how to deliver the curriculum, and ensuring it is done so in a manner that is meaningful and relevant to their pupils. Strengthening teachers' agency in relation to pedagogy, however, can sometimes be difficult to achieve because, for example, of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…When teachers experience psychological safety, they can innovate to maximize their effectiveness, cultivating more creative learning climates (Sun & Huang, 2019). Studies that have evaluated undue restrictions on teachers have led to recommendations to bolster support for their psychological safety (Hughes & Lewis, 2020). Nevertheless, it is clear that establishing a climate of psychological safety in schools is fraught with difficulties (Weiner et al, 2021).…”
Section: Listening and Psychological Safetymentioning
confidence: 99%
“…When teachers experience psychological safety, they can innovate to maximize their effectiveness, cultivating more creative learning climates (Sun & Huang, 2019). Studies that have evaluated undue restrictions on teachers have led to recommendations to bolster support for their psychological safety (Hughes & Lewis, 2020). Nevertheless, it is clear that establishing a climate of psychological safety in schools is fraught with difficulties (Weiner et al, 2021).…”
Section: Listening and Psychological Safetymentioning
confidence: 99%
“…National and international trends in curriculum reform, an undoubtedly complex process, require teachers to serve as agents of reform and to have the freedom to determine how to present a curriculum (Hughes & Lewis, 2020;Priestley, Biesta, & Robinson, 2013). Our case study findings indicated that although some Indonesian elementary school teachers were pessimistic about the outcomes of curriculum reform, which dampened their motivation, other teachers appreciated the objective of the curriculum reform and remained positive about its potential benefits for teachers and students.…”
Section: Discussionmentioning
confidence: 80%
“…Before the new curricula were introduced, both Scotland and Wales had a prescribed curriculum, which means that the flexibility offered to teachers is novel. Although this is widely welcomed by teachers (Hughes and Lewis, 2020;Priestley and Minty, 2013), there are still enduring questions about the extent to which teachers use this flexibility and how the other components of the education system, such as the examination system, encourages them to use such flexibility. In Wales, the Pioneer Schools Network was envisaged as an effective way to achieve this, as evident in some of the pioneer teachers' comments.…”
Section: Conclusion: Current Tensions Similarities and Differences -S...mentioning
confidence: 99%
“…More specifically, the four purposes, the organisation of the content, and the design principles are very similar, although the Es and Os in Scotland are more detailed compared to the Descriptions of Learning in the CfW. The first reaction to the introduction of the new curriculum has been widely positive in both countries, albeit with some cautions and concerns emerging thereafter (Hughes and Lewis, 2020;Priestley and Minty, 2013). However, there was a critical debate in Scotland on the extent of purposeful selection of the four capacities and values, and also the lack of theoretical and conceptual clarity (Priestley and Humes, 2010).…”
Section: Conclusion: Current Tensions Similarities and Differences -S...mentioning
confidence: 99%